Nutritional and bioactive profiles of daylily (Hemerocallis citrina) across flowering stages: A framework for strategic harvest timing - Yuwen Mu; Shenghai Hu; Chunmei Li; Jing Sun; Bei Fan; Fengzhong Wang (Journal of Agriculture and Food Research, 2025)
This study evaluated the impact of different flowering stages on the quality attributes of daylily (Hemerocallis citrina Baroni) flowers. Analysis of samples from three flowering stages (initial, full bloom, and final) revealed distinct biochemical profiles that provide a framework for optimizing harvest timing. The initial flowering stage showed the highest concentrations of multiple compounds. These included phenolics (6.2 ± 0.6 mg/g DW), flavonoids (1.55 ± 0.01 mg/g DW), calcium (3078 ± 1 μg/g DW), and total sugars (190 ± 1 mg/g DW). Full bloom stage exhibited peak concentrations of amino acids (41.05 ± 0.01 mg/g DW), potassium (1982 ± 3 μg/g DW), and magnesium (1392 ± 3 μg/g DW). Phenolic compounds showed U-shaped distribution, decreasing at full bloom before partially recovering during final flowering. Multivariate analysis revealed complex metabolic networks with strong correlations between phenolics and antioxidant activities. OPLS-DA (R2X = 0.95) clearly distinguished distinct metabolic profiles characteristic of each flowering stage. The antagonistic positioning of parameters in the OPLS-DA biplot aligned with negative correlations in the heatmap, confirming metabolic trade-offs throughout development. These findings provide a framework for strategic harvesting: initial flowering maximizes antioxidant properties, full bloom optimizes nutritional content, and final flowering enhances specific flavor compounds, enabling evidence-based decisions to maximize both nutritional value and economic potential.